Wetlands and agriculture: a case for integrated water resource management in Sri Lanka - Atapattu, Sithara S.; de Silva, Sanjiv; Senaratna Sellamuttu, Sonali (2010)
Wetlands are habitats with temporary or permanent accumulation of water. The degradation and loss of wetlands is more rapid than that for other ecosystems, and wetland-dependent biodiversity in many parts of the world is in continuing and accelerating decline. They have been confirmed to deliver a wide range of critical and important services vital for human well-being. Therefore, it is clear that sound wetland management is now expected to not only consider conserving the ecological integrity of the ecosystem but also to pay specific attention to the well-being of local people, thereby contributing to poverty alleviation. Wetlands, both fresh and marine, have a multitude of benefits, in addition to environmental benefits, such as for agriculture, flood control, water purification, fisheries and recreation. For the maintenance and sustainability of wetlands the crucial requirement is water ? a resource that has multiple demands and competition. The main competitor for the water resource around the world is agriculture for food production, a basic requirement for human survival. Therefore, in a situation of wetlands versus food production, the balance tips towards food production without considering the adverse consequences to the wetlands or adequately appreciating the benefits from achieving a balance. This is where Integrated Water Resource Management (IWRM) should be adopted to facilitate this process and enable wetland management and agricultural management to fit into the picture along with the other multiple uses of water. Integrated Water Resource Management should be of considerable interest for Sri Lanka, being a country which has agriculture very high on the agenda. The country is also home to a range of wetlands including 103 distinct river basins and 42 lagoons, which support a multitude of functions and services to people. The relationship between agriculture and wetlands in Sri Lanka is complex. The proliferation of village level water storage structures (small tanks) has created an unusually large number of man-made wetland habitats that add significantly to the natural wetlands that are concentrated mainly in the coastal belt. The absence of an integrated approach to water resource development however, continues to erode natural wetland systems. Two major problems, which concern downstream fisheries and livelihoods, are high levels of agricultural pollution, especially through the excessive use of fertilizers, and modifications to the hydrology. The objective of this paper is to review the work of the International Water Management Institute (IWMI) on wetlands and agriculture in Sri Lanka, to look at the competing water demands between water for wetlands and water required for agriculture, keeping in mind the requirements for nature as well as the sustainability of livelihoods. The paper will address some impacts of agriculture on wetlands, the consequences for livelihoods and the benefits of adopting the IWRM approach, building a case on work carried out in the Kirindi Oya and Bundala wetlands.